A numerical study of temperature effect on the penetration of aluminum foam sandwich panels under impact. (1st December 2017) - Xi, Huifeng; Tang, Liqun; Luo, Shaohong; Liu, Yiping; Jiang, Zhenyu; Liu, Zejia
Abstract: The aluminum foam sandwich is a composite structure with light weight and high specific energy absorption under impact. However, penetrated behaviors of the composite structures at elevated temperatures still remain unclear. A systematic numerical model of the aluminum foam sandwich was developed with the nonlinear, finite element program ABAQUS. In this model, a constitutive relation of aluminum foam with temperature effects was put forward based on uniaxial compressive tests. Subsequently, a failure criterion including both average stress and von Mises stress is obtained through compression, tension and penetration experiments at elevated temperatures. Besides, the eroding contact ensures the touch between the punch and foam core. The numerical model well captured the penetrative process well including the failure features and force-time curves at elevated temperatures. Meanwhile, the energy and max force of aluminum foam sandwich with different mass ratios are discussed. The results disclosed strong temperature effects on the penetrated behaviors of aluminum foam sandwich plates, and reveal the changes of failure modes at elevated temperatures. Highlights: A temperature dependent stress-strain constitutive relation and failure parameters of aluminum foam are developed. Strong temperature effects on the penetrated behaviors of aluminum foam sandwich plates are observed. Penetration behaviors of aluminum foam sandwich with different mass ratios are discussed and optimized.